Incidence and risk factors for suicide attempts in a general population of young people: A Danish register-based study. (March 2013) - Christiansen, Erik; Larsen, Kim Juul; Agerbo, Esben; Bilenberg, Niels; Stenager, Elsebeth
Objective: To estimate the Danish epidemiological long-term incidence rates for suicide attempts in the general population of children and adolescents, and to analyze the impact from single and multiple risk factors on the risk of suicide attempts. Method: We used longitudinal register data from a total cohort of all individuals born between 1983 and 1989 and living in Denmark to calculate incidence rates. From the cohort, we identified all who have attempted suicide, and matched 50 controls to each case. A nested case–control design was used to estimate the impact from risk factors on the risk for index suicide attempts. We established a link to the biological parents and identified risk factors for two generations. Risk factors were analyzed in a conditional logistic regression model. Results: We identified 3718 suicide attempters and 185, 900 controls (189, 618 individuals, aged 10–21 years). We found increasing incidence rates during the period 1994–2005, and higher incidence rates for girls and the oldest adolescents. Mental illness was the strongest independent risk factor (IRR = 4.77, CI = (4.35–5.23), p < 0.0001), but parental mental illness (psychopharmacological drugs: IRR = 1.27, CI = (1.18–1.37), p < 0.0001) and socio-demographic factors (parents not living together: IRR = 1.38, CI = (1.28–1.48), p < 0.0001) were also significant independent risk factors. Exposure to multiple risk factors increased the risk significantly. Conclusions: Suicide attempt is a multi-factorial problem, and a problem on the increase in the period studied. Individuals exposed to multiple risk factors are at the highest risk for suicide attempts, and when spotted or in contact with authorities they should be given proper care and treatment to prevent suicide attempts and death.